Donor contribution to the water and sanitation sector in Palestine - Attili, Shaddad; Palestinian Water Authority (Ramallah Palestinian Water Authority, 2013)
​“The Palestinian Water Authority has prepared this Booklet to highlight the importance of the existing and ongoing cooperation projects funded by international donors in the sector. We also wanted to reflect the outcome of this cooperation and how it has assisted in the development and improvement of the sector.” (at the back of title page)
Keywords: Natural resources; WATER; DEVELOPMENT COOPERATION; INTERNATIONAL COOPERATION; DONORS; PALESTINE; INTERNATIONAL YEARS; Palestinian Water Authority